129k views
5 votes
Help? I can't seem to understand arithmegic sequence.

Help? I can't seem to understand arithmegic sequence.-example-1
User Kristijan
by
5.9k points

1 Answer

3 votes

A sequence
\{a_n\} is arithmetic if the difference between consecutive terms is some fixed number, regardless of which pair of consecutive terms you pick out of the sequence.

For example, the following sequences are arithmetic:

1, 2, 3, 4, 5, 6, ... (difference = 1)

-25, -20, -15, -10, -5, ... (difference = 5)

2. Carla's sequence is not arithmetic, because the differences between consecutive terms are all different:

13 - 11 = 2

17 - 13 = 4

25 - 17 = 8

She can adjust the sequence by changing the last two numbers to 15 and 17, since this makes the difference fixed:

13 - 11 = 2

15 - 13 = 2

17 - 15 = 2

and so on.

3. The sequence

45, 48, 51, 54, ...

is arithmetic with difference 3 between terms. Recursively, we can write the
nth term,
a_n, in terms of the previous,
(n-1)th term,
a_(n-1):


a_n=a_(n-1)+3

By this definition, we can just as easily write the
(n-1)th term in terms of the
(n-2)th term:


a_(n-1)=a_(n-2)+3

Then, substituting this into the previous equation, we have


a_n=(a_(n-2)+3)+3=a_(n-2)+2\cdot3

We can continue this process to write
a_n in terms of
a_1:


a_(n-2)=a_(n-3)+3\implies a_n=a_(n-3)+3\cdot3


a_(n-3)=a_(n-4)+3\implies a_n=a_(n-4)+4\cdot3

and so on. (You might notice that the subscript of the term on the right side, and the number of 3s being added, together sum to
n.) The pattern continues down to


a_n=a_1+(n-1)\cdot3

The first term in this sequence is
a_1=45, so we have

a.
a_n=45+3(n-1)=42+3n

where
n=1,2,3,\ldots.

b. You can fill in the blanks by just adding 3 to the previous term:

45, 48, 51, 54, 57, 60, 63, 66, 69, ...

Then, using the formula found in (a), the 15th term of the sequence is


a_(15)=42+3\cdot15=87

User Arikon
by
5.8k points